Susceptibility weighted imaging can be a sensitive sequence to detect brain damage in neonates with kernicterus: a case report - Maarten Lequin; Floris Groenendaal; Jeroen Dudink; Paul Govaert (BMC Neurology, 2023)
Abstract Background Kernicterus in the acute phase is difficult to diagnose. It depends on a high signal on T1 at the globus pallidum and subthalamic nucleus level. Unfortunately, these areas also show a relatively high signal on T1 in neonates as an expression of early myelination. Therefore, a less myelin-dependent sequence, like SWI, may be more sensitive to detecting damage in the globus pallidum area. Case presentation A term baby developed jaundice on day three following an uncomplicated pregnancy and delivery. Total bilirubin peaked at 542 μmol/L on day four. Phototherapy was started, and an exchange transfusion was performed. ABR showed absent responses on day 10. MRI on day eight demonstrated abnormal high signal globus pallidus on T1w, isointense on T2w, without diffusion restriction, and high signal on SWI at globus pallidal and subthalamus level and phase image at globus pallidal level. These findings were consistent with the challenging diagnosis of kernicterus. On follow-up, the infant presented with sensorineural hearing loss and had a work-up for cochlear implant surgery. At 3 months of age, the follow-up MR shows normalization of the T1 and SWI signals and a high signal on T2. Conclusions SWI seems more sensitive to injury than the T1w and lacks the disadvantage of the T1w sequence, where early myelin confers a high signal.